Secondary Traumatic Stress: Relationship With Symptoms, Exhaustion, and Emotions Among Cemetery Workers - Colombo, Lara; Emanuel, Federica; Zito, Margherita (Frontiers in Psychology, 2019)
Background: Cemeteries workers are deserving of attention because they are exposed to various psychosocial risks: these workers are subject to painful contacts and daily exposed to a work content linked to death experiences and the emotions associated with them. Secondary trauma develops from this continued contact with others’ suffering, operators working with this type of traumatic content and dynamic could experiment emotional disorders (Figley, 1995). Therefore, the secondary traumatic stress is seen as an occupational risk factor (Bride et al., 2004) and cemetery workers are subject to this risk. The studies on the topic have focused on the operators of emergencies, social and health, little attention has been dedicated to cemetery workers. Aim: The present study considers the relations between the dimensions composing the secondary traumatic stress (STS) and the psychological and physical symptoms, the perception of exhaustion, and the positive and negative emotions at work in a group of cemetery workers. Moreover, differences among occupational tasks are explored considering the different possibilities of contact with clients and trauma contagion. Method: 114 participants in a cemetery organization in northern Italy, divided into technicians employees /TE), technicians and specialists of decoration and garden (TS), gravediggers (GR) administrative and front office employees (AFO), have completed a self-report questionnaire. Levels of secondary trauma and psychophysical symptoms were assessed, and correlations were calculated in the total sample and for the different categories of operators. Results: AFO and TS showed the the highest levels of secondary traumatic stress and psychophysical symptoms, in particular for symptoms related to anxiety, sadness, insomnia and gastric and musculoskeletal disorders. Conclusion: This study highlights the importance of considering the secondary traumatic stress among also this category of workers, since they are exposed daily not only with death, but also with suffering people that are often asking for grief and emotional skills that cemetery workers are not trained to give. It is important to monitor symptomatic levels to avoid chronicity, but also to provide employees with psychological support and training about secondary trauma and its consequences.